The Magic of Pyramid Firms: Cosmologies of Speculation, Repertoires of Credit and Collapsed Finance. Issue 2 (15th March 2019) - Musaraj, Smoki
ABSTRACT: International media accounts of the spectacular collapse of the pyramid firms in Albania in 1997 centre on the story of Maksude Kadëna, the head of the notorious firm, Sude. These accounts depict Kadëna as a 'gypsy fortune teller who claimed to look into a crystal ball'. In this article, I return to these various accounts of Sude/Kadëna as a way to explore ethnographically the broader set of cosmologies and repertoires of credit and speculation that informed the decisions and strategies of participation in these firms. I suggest that the activities of the firms were, on the one hand, an extension of practices and ideas about the free market during the communist regime and, on the other hand, a manifestation of postsocialist cosmologies or risk and speculation and repertoires of credit and investment that extended well beyond the firms.